NSAID Conjugates with Carnosine and Amino Acids - Sahu, Sandhyamayee; Panda, Siva S.; Asiri, Abdullah M.; Katritzky, Alan R. (Synthesis, 2013)
Benzotriazole-mediated syntheses of novel bioconjugates of nonsteroidal anti-inflammatory drugs with carnosine and with amino acids were prepared in yields of 50–97% as potential drug candidates.
Keywords: NSAIDs; carnosine; amino acid; prodrug; conjugates; coupling; benzotriazole methodology